ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMPN 9 KABUPATEN MUARO JAMBI - Laksana, Tirta Yatra Jaya; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2020)
Currently, the processing of administrative data for fund of Operational Aid to School Program (BOS) atSMPN 9 Kab. Muaro Jambi is still done with conventional way, i.e. by using Ms. Excel. The weakness ofusing this way is human error that often occurs when processing the data, such as doing mistake wheninputting the data to fulfill the requirement of form, standard, and template of report of Operational Aid toSchool Program. The purpose of this study is to analyze the problem of the administrative and informationsystem of Operational Aid to School Program (BOS) at SMPN 9 Kab. Muaro Jambi, and to create a designof system of administrative information for Operational Aid to School Program (BOS) in that school. Thedesign is created by using visual paradigm and object-based modelling technique to illustrate the analysisand design of system, i.e. in the form of use case diagram, class diagram and activity diagram. This studyresults a design of prototype analysis system and administrative information system for Operational Aid toSchool Program in SMPN 9 Kab. Muaro Jambi. This prototype needs to be developed further in the nextstudy so that it can be applied by completing security data system